AI in Consulting Services : Applications, Challenges, and Ethical Insights - Lari, Halima Afroz; K. S., Manu (Indian Journal of Computer Science, 2024)
The rapid advancement of Artificial Intelligence (AI) and generative AI technologies is transforming industries worldwide, and the consulting sector is no exception. This research paper provides a comprehensive exploration of how AI is reshaping the consulting landscape. The study begins with an introduction to AI and generative AI, highlighting their potential to revolutionize various aspects of business and technology. It then offers an overview of the global consulting sector, emphasizing the critical role of management consulting in driving business strategy, innovation, and organizational efficiency. The study delves into the integration of AI into consulting services, discussing how AI tools and technologies are being adopted to enhance the value and effectiveness of consulting engagements. A detailed literature review is presented, analyzing existing research on AI applications in consulting, and identifying key trends and developments in the field. The study categorizes the applications of AI in consulting into several key areas: automation of routine tasks, improving decision-making processes, providing customized client services, developing novel business strategies, and optimizing supply chain operations. These applications demonstrate AI’s ability to significantly enhance the efficiency, accuracy, and scope of consulting services. Practical use cases from leading global consulting firms, such as Boston Consulting Group (BCG), PricewaterhouseCoopers (PwC), Ernst & Young (E&Y), Infosys, and IBM, are examined to illustrate how AI is being implemented in real-world consulting scenarios. These examples showcase how AI-driven solutions are being utilized to solve complex business problems, enhance client engagement, and deliver innovative services that were previously unattainable. The research also addresses the ethical challenges associated with the implementation of AI in consulting. Key ethical concerns discussed include the need for transparency and disclosures in AI-driven recommendations, the importance of privacy and data protection, the risk of bias in algorithmic decision-making and the implications of AI training methodologies. To conclude, the paper asserts that AI is making a positive and transformative impact on the consulting sector. It emphasises that AI is not only enhancing the capabilities of consulting firms but also driving significant changes in how consulting services are delivered, thereby creating new opportunities for innovation and growth. The study underscores the importance of addressing the ethical considerations associated with AI to ensure that its integration into consulting services is both effective and responsible.